Metal Boride‐Based Catalysts for Electrochemical Water‐Splitting: A Review. (30th October 2019) - Gupta, Suraj; Patel, Maulik K.; Miotello, Antonio; Patel, Nainesh
Abstract: Electrocatalytic water‐splitting has gained a firm hold in the area of renewable hydrogen production owing to its integrative compatibility with intermittent energy sources. However, wide‐scale implementation of this technology demands discovery of new electrode materials that strike a good balance between efficiency, stability, and cost. In the pool of inexpensive electrodes capable of catalyzing hydrogen and oxygen evolution reactions, metal borides/borates have made a big splash in the last decade. However, the research in this family of electrocatalysts remains unorganized owing to the diversity of reports. This review summarizes the past and present research progress in metal borides/borates for electrocatalytic water‐splitting. The fundamental reasons for electrochemical behavior in different metal borides/borates are highlighted here, also including some comments regarding erroneous practices in the performance evaluation of metal borides/borates. Various strategies used to enhance the electrocatalytic performance of metal borides/borates are discussed in detail. Different methods evolved over the years for the synthesis of metal borides/borates are also discussed. Finally, an assessment of the commercial viability of metal borides/borates is made and future research directions are suggested. Abstract : The unprecedented emergence of metal borides/borates as a highly efficient family of materials for electrocatalytic water‐splitting is reviewed. A discussion on the theories to understand their reaction mechanism, various material engineering strategies to improve their performance, and different synthesis routes for their fabrication is included in the review. A concrete future perspective is provided for further research and development.